Sickle cell disease induces resistance to cutaneous carcinogenesis - Boutros Soutou (Orphanet Journal of Rare Diseases, 2020)
Abstract Background While skin carcinomas are reported in chronic ulcers and in patients treated with hydroxyurea (HU) for myeloproliferative neoplasms, no skin carcinoma has been reported in patients with sickle cell disease (SCD), presenting chronic skin ulcers or treated with HU. The objective was to estimate the risk of cutaneous malignant transformation in SCD patients with prolonged leg ulcers or under HU therapy. Results In this cross-sectional study, the cohort consisted of 1543 patients. In the first series, 29 patients presented a total of 53 ulcers lasting more than two years. The median age was 35 ± 8.4 years old. The median duration for a single ulcer was 9.2 ± 7 years. None of the examined ulcers showed any suspicious area of malignant transformation. In the second series, 187 patients treated with HU for more than two years were identified. The median age was 31.3 ± 9.9 years old. The median duration of treatment with HU was 6 ± 3.2 years. No skin carcinoma or actinic keratosis was recorded. Conclusions This study showed that skin carcinogenesis did not occur in our series of SCD patients exposed to transforming events such as long term HU treatment or prolonged leg ulcers.